Tekanan Eksternal, Faktor Politik, Pengendalian Internal Dan Gaya Kepemimpinan Dalam Meningkatkan Transparansi Pelaporan Keuangan Pemerintah Daerah - Yesi Mutia Basri; Vini Zenita; Rofika Rofika (Universitas Islam Bandung, 2021)
This study aims to test and prove whether external pressures, political factors, internal control and leadership styles have an influence on financial reporting of local government transparency. This research was conducted in OPD Siak district. The total population was 33 DPOs, all DPOs were sampled. The data used are primary data with a questionnaire as an instrument. Purposive sampling as a sampling method. The number of samples is 99 respondents. Respondents in this study were selected with several criteria, namely: (1) echelon II, III, IV officials who work in the Siak Regency government, (2) have a minimum work experience of 1 year, (3) financial employees who have worked for at least 1 year , because it is considered that they have experience and already know the developments in the OPD in Siak Regency. Multiple linear regression as a data analysis technique and assisted by SPSS ver.20.0 for windows. The results prove that the political factors, internal control and leadership style variables have a positive effect on financial reporting transparency. The external pressure variable has a negative effect on financial reporting transparency. The results of this study are useful for developing insights and providing in-depth understanding relating to financial reporting transparency influenced by external pressures, political factors, internal control, and leadership styles. It is also hoped that it can become a reference material for comparison information for other studies that wish to discuss this issue, and it is hoped that it will become an alternative for the government in evaluating the transparency of financial reporting, especially local governments in Siak Regency.